Correlation between 6-minute walk distance and spirometry parameters in stable chronic obstructive pulmonary disease patients - Hajare, Ruchita B.; Nagarwala, Raziya; Shyam, Ashok; Sancheti, Parag (International Journal of Research in Medical Sciences, 2018)
Background: Six minute walk test (6MWT) is a sub-maximal exercise test, used as a clinical indicator of the functional capacity, in patients with cardiopulmonary diseases. It is simple, objective and reproducible test. The present study was designed to assess correlation of six minute walk test with spirometry parameters, in patients with chronic obstructive pulmonary disease. Methods: In this cross sectional study, fifty patients diagnosed with chronic obstructive pulmonary disease (GOLD criteria) coming to tertiary center were recruited according to inclusion and exclusion criteria. All patients underwent spirometric measurement. Spirometric indices including FEV1, FVC, FEV1/FVC and MVV were tested using computerized spirometer. 6MWT was performed following American Thoracic Society (ATS) guidelines. Percent (%) predicted 6MWD was calculated. Correlation between spirometry and 6MWT was assessed. Results: It was found that correlation between 6MWT and spirometry is statistically significant. There is significant strong positive correlation between percent predicted 6MWD and FEV1 (r=0.850 and p= <0.001), whereas there is significant moderate correlation between percent predicted 6MWD and FVC (r=0.554 and p= <0.001), FEV1/FVC (r=0.509 and p= <0.001) and MVV (r=0.615 and p= <0.001). Conclusions: In chronic obstructive pulmonary disease, percent predicted 6mwd significantly correlated with the spirometry parameters (FEV1, FVC, FEV1/FVC, and MVV). 6MWD decreases as there is decline in the pulmonary function. 6MWT can be a useful replacement of spirometry in assessment of severity of COPD.